Personality traits and transition to psychosis one year after the first assessment - De Salve, Francesca; Rossi, Chiara; Cavalera, Cesare; Malvini, Lara; Barbera, Simona; Tagliabue, Sofia; Percudani, Mauro; Oasi, Osmano (Frontiers in Psychology, 2023)
Introduction Several studies have identified ultra-high-risk criteria that may characterize an at-risk mental state and predict the transition of psychotic evolution. Personality traits may play a crucial role in this process. Aims The current study aims to: (a) explore the evolution of an initial diagnosis over 12 months; (b) assess differences in social and occupational functioning; (c) identify common (trans-diagnostic) personality traits of psychotic risk. Methods The sample includes 97 (44 males and 53 females) young adults. They completed an assessment that consists of socio-demographic data, the Social and Occupational Functioning Scale, the Early Recognition Inventory-retrospective assessment onset of schizophrenia, and the Personality Inventory for DSM-5 (PID-5). According to the tests’ assessment, the sample was divided into three different groups: Ultra-High Risk (UHR), At-Risk, and Not at risk. One year after the first evaluation, psychiatrists administered the QuickSCID-5 to verify the diagnostic trajectories of the sample. Results Overall, the most prevalent category diagnoses were anxiety/depression, personality disorders, and psychosis. Specifically, the most common diagnosis in the UHR group was psychosis. Moreover, in the UHR group, the social and occupational functioning score was the lowest. In terms of differences in PID-5 personality traits, the At-risk and UHR groups scored highest in detachment and disinhibition. No statistically significant differences were found between the groups for negative affectivity, antagonism, and psychoticism traits. Conclusion Results obtained by the current study should be considered an attempt to better understand the diagnostic trajectories and trans-diagnostic personality traits in a group of young help-seekers, specifically in UHR. Findings highlight both the importance of diagnosis and personality traits evaluation to customize a specific intervention based on the level of psychotic risk. Clinical suggestions are reported.